2021
DOI: 10.5489/cuaj.7313
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of robotic radical cystectomy functional and quality of life outcomes

Abstract: This systematic review summarizes the urinary continence, male sexual function, and female sexual function outcomes after robotic-assisted radical cystectomy (RARC). Greater intracorporeal diversion use, longer followup, and clearly stated urinary continence definitions have revealed RARC urinary continence rates for orthotopic ileal neobladders that are similar to those after open radical cystectomy (ORC) when using the strictest continence definitions. Nerve-sparing technique appears to be well-used in most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Our initial review also demonstrated that surgical approach for radical cystectomy did not have a significant impact on patient-important outcomes [ 9 ]. The results from other systematic reviews that also included non-randomised studies were consistent with these findings [ 23 , 24 ]. Therefore, both RARC and ORC can be considered to be equivalent in the wider sense with the decision on approach based on surgeon experience/training, accessibility and health economics.…”
Section: Discussionsupporting
confidence: 81%
“…Our initial review also demonstrated that surgical approach for radical cystectomy did not have a significant impact on patient-important outcomes [ 9 ]. The results from other systematic reviews that also included non-randomised studies were consistent with these findings [ 23 , 24 ]. Therefore, both RARC and ORC can be considered to be equivalent in the wider sense with the decision on approach based on surgeon experience/training, accessibility and health economics.…”
Section: Discussionsupporting
confidence: 81%
“…summarized that the QoL outcomes were similar between RARC and ORC. 46 Fuschi et al. revealed that the rates of complications of intracorporeal UD were 37.4% of single stoma ureterocutaneostomy and 57.6% of IC.…”
Section: Discussionmentioning
confidence: 99%
“…45 Jue et al summarized that the QoL outcomes were similar between RARC and ORC. 46 Fuschi et al revealed that the rates of complications of intracorporeal UD were 37.4% of single stoma ureterocutaneostomy and 57.6% of IC. 47 In our study, all patients underwent laparoscopic RC plus extracorporeal UD and the rate of late complication was 42.9% (MSSCU) and 43.5% (IC), which was nearly consistent with previous study.…”
Section: T a B L Ementioning
confidence: 99%
“…Robotic-assisted laparoscopic radical cystectomy (RARC) was introduced in 2003. Although its use has rapidly increased, randomized controlled trials have shown similar perioperative outcomes and complication rates between traditional open radical cystectomy (ORC) and RARC methods [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…The potency rates after RC range between 14% and 80% and are comparable between ORC and RARC series [ 19 , 49 , 51 ]. Nerve-sparing techniques preserve the autonomic nerves involved in erectile function, improving potency compared to standard RC [ 6 , 50 , 51 ] without compromising oncological outcomes. Rates of post-RC ED are estimated to be 10–30% after NS techniques and 80–90% following the use of standard technique [ 6 ].…”
Section: Introductionmentioning
confidence: 99%